Analysis Of Product Quality in love Tempe – Cemara Asri With Quality Function Deployment Method - Sintya; Susanto (Simangunsong : Journal of Business Administration, Management, Economic And Accounting, 2024)
This research entitled "Analysis of Product Quality in Love Tempe - Cemara Asri with Quality Function Deployment Method". Love Tempe is a NON GMO tempe production house which has a very high protein content so it is good for the body. The purpose of this study was to analyze Quality Function Development in an effort to improve the quality of Love Tempe – Cemara Asri products. The method used by the author is descriptive quantitative. The analysis of this research measurement tool uses validity, reliability, and Quality Function Deployment tests. The number of respondents in Love Tempe - Cemara Asri is 97 customers using the Lemeshow calculation formula. The data analysis used is the Quality Function Deployment (QFD) with the help of the House of Quality matrix. The results of this study indicate that the attributes that need to be considered by Love Tempe to meet the needs and desires of consumers are that tempe is always new and fresh, made from selected soybeans, the texture of tempe is soft, hygiene in the production process, NON GMO certification and labeling, appearance of tempe. in accordance with the menu list, the taste of the product is in line with expectations, the production house is clean and comfortable, employees can handle complaints and satisfy customers, the quality of tempe is in line with expectations, the packaging design is attractive, the ease of getting products, the fermentation room is very sterile (29- 30 degrees), tempeh does not fail in production, the shelf life of tempe is longer, and the durability of tempe in the freezer. At the level of technical needs, the requirements that need to be carried out by Love Tempe are the use of quality raw materials, maintaining and improving the cleanliness of rooms and products, improving the quality control inspection process, improving the product design of love tempe, the process of making tempe in accordance with standards, employee training in serving consumers , online product marketing, and increasing the durability of tempe with quality control.